Nitrogen-enriched activated carbon derived from plant biomasses: a review on reaction mechanism and applications in wastewater treatment - Bumajdad, Ali; Khan, Mohammad Jakir Hossain; Lukaszewicz, Jerzy P. (Frontiers in Materials, 2023)
As a key kind of evolving carbonaceous adsorbent, nitrogen-enriched activated carbon (NEAC) has drawn a lot of focus due to its better physiochemical ability to eliminate an extensive range of wastewaters contaminants under severe conditions. Its environment-friendly character is one more reason behind this focus. Nitrogen also has immense effect on AC structures' pollutants adsorption capability; therefore, it is an area of interest. Reports concerning the reaction pathway of C-N (carbon-nitrogen) bond creation on AC surface are limited. Determining such mechanisms is challenging but critical to understand bond characteristics after carbonization. Moreover, it is vital to ascertain real-time kinetics concerning adsorption phenomena in liquid phase. Such a latest trend indicates that regulated nitrogen uses for carbonaceous substances having a biomass-based origin can provide the desired morphological characteristics produced through interconnections, production of enclosed holes, enhanced surface area, better adsorption ability, and many other benefits in contrast to conventional carbon-based substances. This review points out the developments in the main processes to introduce nitrogen atoms into the carbon matrix by utilizing different N-comprising chemical compounds. The nitrogen enrichment processes, reaction mechanisms and effects of nitrogen incorporation on the plant biomassderived activated carbons (NEACs) are presented in brief. On the basis of their established physicochemical attributes, the adsorption performances of different biomass-derived NEACs have also been dealt with. More significantly, the review covers the technical issues in the present phase, topical trends, research gaps, economic viability along with a technical alignment recommendation to address the prevailing disadvantages.